(untitled) (Contemporary Mathematics, 2025)
The assessment of combat system capabilities and the identification of critical nodes are focal points in the research of combat systems. This paper investigates the issue of identifying critical nodes within combat systems based on the construction of a combat system model and capability assessment. It proposes a method for constructing a combat system network model based on the number of connections between nodes, taking into account the impact of combat time on system capabilities. A time efficiency coefficient is introduced to develop a capability assessment model that incorporates time efficiency. Furthermore, a method for identifying critical nodes based on effectiveness betweenness centrality is proposed. Simulation results indicate that the combat system network model and capability assessment methods presented in this paper are valid, and the accuracy of the critical node identification method based on effectiveness betweenness centrality is high.